Lagenorhynchus obscurus - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Lagenorhynchus obscurus (Gray, 1828). Spicil. Zool., 1:2. TYPE LOCALITY: South Africa, Cape Prov., Cape of Good Hope. DISTRIBUTION: Coastal temperate waters of the Southern Hemisphere. COMMENT: Included in cruciger by Hershkovitz, 1966:65, but considered a distinct species by Rice, 1977; Brownell, 1974, in Brown, et al., eds., Antarctic Mammals, Folio 18, Amer. Geogr. Soc., 19 pp. 11 pls.; IWC, 1975, J. Fish Res. Bd. Can., 32:875-983. Includes fitzroyi; see Rice, 1977. PROTECTED STATUS: CITES - Appendix II as Order Cetacea. ISIS NUMBER: 5301411002012006001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Cetacea, pp. 290-304 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on pages 293-294, DOI: 10.5281/zenodo.7352983